Gold Nanoparticle Coated Carbon Nanotube Ring with Enhanced Raman Scattering and Photothermal Conversion Property for Theranostic Applications - Song, Jibin (J Am Chem Soc, 2016)
We report a new type of carbon nanotube ring (CNTR) coated with gold nanoparticles (CNTR@AuNPs) using CNTR as a template and surface attached redox-active polymer as a reducing agent. This nanostructure of CNTR bundle embedded in the gap of closely attached AuNPs can play multiple roles as a Raman probe to detect cancer cells and a photoacoustic (PA) contrast agent for imaging-guided cancer therapy. The CNTR@AuNP exhibits substantially higher Raman and optical signals than CNTR coated with a complete Au shell (CNTR@ AuNS) and straight CNT@AuNP. The extinction intensity of CNTR@AuNP is about 120-fold higher than that of CNTR at 808 nm, and the surface enhanced Raman scattering (SERS) signal of CNTR@AuNP is about 110 times stronger than that of CNTR, presumably due to the combined effects of enhanced coupling between the embedded CNTR and the plasmon mode of the closely attached AuNPs, and the strong electromagnetic field in the cavity of the AuNP shell originated from the intercoupling of AuNPs. The greatly enhanced PA signal and photothermal conversion property of CNTR@AuNP were successfully employed for imaging and imaging-guided cancer therapy in two tumor xenograft models. Experimental observations were further supported by numerical simulations and perturbation theory analysis.